Fruit ripeness in relation to storability for medicinal product development and seed viability of Phaleria macrocarpa / Suaad Mohamed Ahmed Asrity - Ahmed Asrity, Suaad Mohamed (Institute of Graduate Studies, UiTM, 2016)
Phaleria macrocarpa, or also known as Mahkota Dewa, is popular medicinal plant in Indonesia and has recently been introduced in Malaysia in view of its commercial potential as health supplements. Many studies have focused on the active compounds in fruit, which is primarily used in medicinal products, but postharvest handling of the fruits has not been well documented. Studies were, hence, carried out to determine the relationship between fruit ripeness, morphological and chemical properties, and changes during fruit storage prior to product development for safety and optimum health benefits. Besides, the seeds within them are also primary means of propagation as vegetative multiplication of this plant species is of low success. Results showed that fruit of drupe of this medicinal plant had respiration rate, size and weight increased while become more juicy as ripening progressed from full size unripe to fully ripe stage. It is probably a climacteric fruit. Antioxidant contents in terms of ascorbic acid and total phenolic contents were, however, lower with fully ripe fruits as compared to half ripe and unripe fruits. Most fully ripe fruits also had insect pest and microbial damages in pericarp and mesocarp, making them unsuitable for product development. Subsequent studies on fruit storage for medicinal products were, hence, only conducted with unripe and half ripe fruits. These fruits were short lived with refrigeration storage at 8±2°C. Fruits packed in perforated polythene bags could be stored for only two weeks while vacuum packaging could keep the fruits for longer period of four weeks with acceptable 5% damage. Fruits exhibited lower titratable acidity and ascorbic acid content but soluble solids increased following storage in the refrigerator…